IMPLEMENTASI METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SDN 002 BINTAN TIMUR - sodari, sodari (UNIVERSITAS TANJUNGPURA, 2024)
This study aims to determine whether the implementation of the inquiry method in the learning process can improve math learning outcomes for class IV C students at SD Negeri 002 Bintan Timur. The inquiry method makes math subjects more engaging and allows students to directly identify scientific concepts and principles clearly. This approach helps students grasp important concepts in math learning. This classroom action research was conducted at SD Negeri 002 Bintan Timur during the 2022/2023 academic year, with a sample of 22 students from class IV C. Data collection techniques used were tests and observations. The tests were used to gather data on students' mastery and understanding (cognitive aspect through objective tests consisting of multiple-choice and essay questions. Observations were conducted to assess the students' learning outcomes in the affective and psychomotor aspects. Based on the research results, it can be concluded that the implementation of the inquiry method in learning, following the steps outlined in the lesson plan, can improve students' learning outcomes in cognitive, affective, and psychomotor aspects. A recommendation for math teachers based on this research is to combine inquiry with other innovative teaching models or methods to prevent students from becoming bored.